Queen Victoria and Prince Albert: Constructing a Sustainable Monarchy and Negotiating Gender and Foreignness Under Conditions of precarity - Caswell, Tia E. C. (2022)
Although many writers have commented on Queen Victoria’s role as a female monarch and the anxieties associated with female rule – authors such as Thompson (2001), Munich (1987) and Homans (1993) provide an in-depth account of Queen Victoria as a powerful female figure – there has been little discussion of Queen Victoria’s and Prince Albert’s reception as German figures of monarchical power. This dissertation examines the extent to which Queen Victoria’s and Prince Albert’s German heritage affected their public reception, particularly against the backdrop of political precarity. I argue that Queen Victoria and Prince Albert utilised royal iconography and portraiture in order to gain the approval of their subjects and to demonstrate that they were capable of sustaining the monarchy at a politically precarious time. To set the scene, the dissertation first discusses how far Britain/the British political system can be perceived as precarious in an age defined by revolutionary thought and reformatory action, before moving on to present the development of the nineteenth-century feminine ideal and its portrayal in English and German literature. My discussion of nineteenth-century gender ideals represented in royal portraiture demonstrates how such iconography was used by Victoria to construct an image of herself as the maternal monarch with a chivalrous German husband. In Chapter Three, I consider the royal couple’s split identities: Queen Victoria was a female figure of power with a German heritage linked in marriage to a German husband and male consort Prince Albert. The intersectionality associated with Victoria’s and Albert’s foreignness will be analysed in relation to Victoria’s and Albert’s seemingly “upside-down” or unconventional gender roles. I argue that Queen Victoria and Prince Albert used royal iconography, photography, and portraiture to manage their public reception and deflect public anxieties relating both to their foreignness and their gender unconventionality. Finally, I will reflect on the extent to which Victoria and Albert succeeded in constructing a sustainable monarchy under conditions of precarity.